Accounting Conservatism and Firm Structure in Nigeria: Evidence from Publicly Listed Manufacturing Firms - Ogiriki Tonye; Suwari Preteowei Topman (International Journal on Economics, Finance and Sustainable Development, 2022)
This paper assessed the relation between accounting conservatism and firm structure in Nigeria. The expo facto research design was adopted and a sample of thirty-eight (38) publicly listed manufacturing firms was employed. Data of accounting conservatism (earnings accrual) and firm structure (equity-to-asset and asset tangibility ratios) were obtained from 2012-2020. The Fixed (FE) and Random effects (RE) regression statistical technique was used. We find evidence that a firm with more conservative financial disclosure of its earnings accrual adjusts its asset structure towards the companies target more rapidly; this in particular is common for publicly listed manufacturing firms that rely on external financing for adjustment. Moreover, we found that the level of accounting conservatism positively and significantly affects the firm structure and this effect arises due to debt issuance. Overall, the paper suggests that the level of accounting conservatism plays a vital role in enhancing under-levered firms’ adjustment of asset structure of publicly listed manufacturing firms in Nigeria.